Charge localization increases chemical expansion in cerium-based oxides - WATSON, GRAEME; MARROCCHELLI, DARIO (My University, 2012)
In this work, we demonstrate the mechanism by which electronic charge localization increases the chemical expansion coefficient in two model systems, CeO 2-? and BaCeO 3-?. Using Density Functional Theory calculations, we predict that this coefficient is increased by more than 70% when charge is fully localized, consistent with the observation that materials with a smaller degree of charge localization have smaller chemical expansion coefficients. This finding has important consequences for devising materials with smaller chemical expansion coefficients and for the reliability of the widely-used Shannon's ionic radii
PUBLISHED
Keywords: Density Functional Theory; Density Functional Theory